MODELING OF GEOMETRIC OBJECTS BY MEANS OF COMPUTER TECHNOLOGIES - Цвіркун, Людмил; Омельченко, Олександр; Цвіркун, Сергій; Лісовий, Сергій (SWorldJournal, 2025)
The article states that information technologies are a powerful means of forming the professional competence of a future engineer. Information technologies expand the possibilities of the educational environment by using various computer technologies aime